Serbian Literature and Emigration of Bosnian- Herzegovinian Muslims during Austro-Hungarian Rule - Šaljić Ratković, Jovana (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
of Bosnia and Herzegovina, which until then had been under the rule of the Muslim Ottoman Empire. The Muslim population that lived in the province, although of Slavic origin, language and customs, used to live for centuries in an Islamic cultural circle, which is why they considered every non-Muslim government in the province to be an infidel. With the withdrawal of the Ottoman administration from the Balkan peninsula in the 19th and early 20th century, they found themselves in a dilemma: the West or the East, the nation or the religion? While trying to lead them to a decision, young Balkan national states, including the Principality of Serbia, began with the general cultural, political and social project known as “the nationalization of Muslims”, considering this population to be a part of their own national identity connected to it by a common language and ethnic background. Therefore, the emigration of the Slavic Muslims from Bosnia and Herzegovina to the Ottoman Empire was by no means in the interest of the Serbian authorities, who were trying to prevent such a mass phenomenon.Since political activities from Serbia were usually forbidden at that time in Bosnia and Herzegovina due to complicated foreign policy relations with the Austro-Hungarian Empire, the Serbian side carried out its breakthrough towards Muslims primarily through culture, especially literature and literary magazines. In particular, two examples of Serbian literature referred to the emigration of Muslims, in an effort to dissuade them from such an act. The first example is the poem Stay Here by the famous Serbian poet and writer Aleksa Šantić, published in 1896 in the literary magazine “Zora”, while the second example is the lesser known but extremely impressive engaged drama Muhajir by the Serbian writer, poet and public worker Osman Djikic, the most famous representative of the Bosnian Muslims who called themselves the “Serbs of the Muslim faith”.Serbian literature in the second half of the 19th century played a significant role in national efforts among Bosnian Muslims, especially among the educated youth who called themselves Serbs of the Muslim faith. However, when viewed with the benefit of time – although in contradiction with both Islamic theory and European practices – religion prevailed as a crucial factor in shaping the national identity of the majority of the South Slavic Muslims while around 140,000 Muslims moved out from Bosnia and Herzegovina during the Austro-Hungarian government in that province.